Biodiversity of cave-dwelling organisms in peninsular India (Zoological Records and Reviews, 2023)
Cave ecosystems -- encompassing limestone karst caves, granite boulder caves, sandstone rock shelters, and lava tubesystems -- represent some of Earth's most extreme and biologically distinctive habitats, harbouring highly specialisedfauna adapted to permanent darkness, reduced food inputs, high humidity, and stable temperatures. Peninsular India,with its extensive limestone formations in Andhra Pradesh and Telangana, granite inselberg complexes across theDeccan, and basalt lava formations of the Deccan Traps, hosts a significant but poorly documented cave fauna. Thisstudy presents the first systematic multi-cave, multi-taxon biodiversity assessment of cave-dwelling organisms from 28cave systems across peninsular India, encompassing troglobitic (obligate cave-dwelling), troglophilic (facultativecave-dwelling), and trogloxenic (cave-visiting) fauna surveyed using standardised transect searches, pitfall arrays, andbat acoustic monitoring. A total of 184 animal species are documented, including 42 troglobitic species representingobligate cave specialists. Eighteen species are candidate new species, all obligate cave-dwellers from limestone karstsystems. Bat diversity is the highest component with 28 species documented across all cave types. Cave area, degree ofisolation, and substrate type are the strongest predictors of troglobitic species richness. Twelve species are IUCNThreatened. Quarrying, tourism, and guano mining are identified as the primary threats to peninsular Indian cavebiodiversity.